Perkawinan Beda Agama Yang Dilakukan Di Luar Negeri Berdasarkan Hukum Positif Di Indonesia - Soebandi -; Benny Haryono (Universitas Mahendradatta, 2020)
Every religion has provisions governing marriage, so everyone must obeyand be asked for their respective religions. Every Indonesian citizen who marries mustgo through their respective religious institutions. Because marriages based on birthbonds can be accepted as valid, it has been agreed to fulfill in Article 2 paragraph (1) ofLaw Number 1 of 1974, how legal marriages are conducted according to the law of eachreligion and its beliefs. Therefore, marriages must be carried out according to the law ofeach religion and belief, otherwise the marriage is not valid. While all religions inIndonesia do not allow marriages to be held if the two candidates are of differentreligions. For example, for Christians interfaith marriages are not legal, because theyare carried out according to the rules of the Christian religion not in accordance withthe conditions set out in the marriage. Every religion approved in Indonesia. Expellingeveryone to do a marriage different from religion is not in accordance with Indonesianreligious and national law.